Identification and Characterization of IMD-0354 as a Glutamine Carrier Protein Inhibitor in Melanoma - Feng, Yongmei (Mol Cancer Ther, 2021)
A key hallmark of cancer, altered metabolism, is central to cancer pathogenesis and therapy resistance. Robust glutamine metabolism is among cellular processes regulating tumor progression and responsiveness to therapy in a number of cancers, including melanoma and breast cancer. Among mechanisms underlying the increase in glutamine metabolism in tumors is enhanced glutamine uptake mediated by the glutamine transporters, with SLC1A5 (also known as ASCT2) shown to play a predominant role. Correspondingly, increased SLC1A5 expression coincides with poorer survival in breast cancer and melanoma patients. Therefore, we performed an image-based screen to identify small-molecules that are able to prevent the localization of SLC1A5 to the plasma membrane without impacting cell shape. From 7,000 small molecules, 9 were selected as hits, of which one (IMD-0354) qualified for further detailed functional assessment. IMD-0354 was confirmed as a potent inhibitor of glutamine uptake that attained sustained low intracellular glutamine levels. Concomitant with its inhibition of glutamine uptake, IMD-0354 attenuated mTOR signaling, suppressed 2D and 3D growth of melanoma cells, and induced cell cycle arrest, autophagy and apoptosis. Pronounced effect of IMD-0354 was observed in different tumor derived cell lines, compared with non-transformed cells. RNAseq analysis identified the unfolded protein response, cell cycle and DNA damage pathways to be affected by IMD-0354. Combination of IMD-0354 with GLS1 or LDHA inhibitors enhanced melanoma cell death. In vivo, IMD-0354 suppressed melanoma growth in a xenograft model. As a modulator of glutamine metabolism, IMD-0354 may serve as an important therapeutic and experimental tool that deserves further examination.